A review on biochar modulated soil condition improvements and nutrient dynamics concerning crop yields: Pathways to climate change mitigation and global food security. (July 2019) - Purakayastha, T.J.; Bera, T.; Bhaduri, Debarati; Sarkar, Binoy; Mandal, Sanchita; Wade, Peter; Kumari, Savita; Biswas, Sunanda; Menon, Manoj; Pathak, H.; Tsang, Daniel C.W.
Abstract: The beneficial role of biochar on improvement of soil quality, C sequestration, and enhancing crop yield is widely reported. As such there is not much consolidated information available linking biochar modulated soil condition improvement and soil nutrient availability on crop yields. The present review paper addresses the above issues by compilation of world literature on biochar and a new dimension is introduced in this review by performing a meta-analysis of published data by using multivariate statistical analysis. Hence this review is a new in its kind and is useful to the broad spectrum of readers. Generally, alkalinity in biochar increases with increase in pyrolysis temperature and majority of the biochar is alkaline in nature except a few which are acidic. The N content in many biochar was reported to be more than 4% as well as less than 0.5%. Poultry litter biochar is a rich source of P (3.12%) and K (7.40%), while paper mill sludge biochar is higher in Ca content (31.1%) and swine solids biochar in Zn (49810 mg kg −1 ), and Fe (74800 mg kg −1 ) contents. The effect of biochar on enhancing soil pH was higher in Alfisol, Ferrosol and Acrisol. Soil application of biochar could on an average increase (78%), decrease (16%), or show no effect on crop yields under different soil types. Biochar produced at a lower pyrolysis temperature could deliver greater soil nutrient availabilities than that prepared at higher temperature. Principal component analysis (PCA) of available data shows an inverse relationship between [pyrolysis temperature and soil pH], and [biochar application rate and soil cation exchange capacity]. The PCA also suggests that the original soil properties and application rate strongly control crop yield stimulations via biochar amendments. Finally, biochar application shows net soil C gains while also serving for increased plant biomass production that strongly recommends biochar as a useful soil amendment. Therefore, the application of biochar to soils emerges as a 'win-win strategy' for sustainable waste management, climate change mitigation and food security. Highlights: Nutrient value of various biochar is discussed. Impact of biochar on improvement of soil pH, CEC and buffering system delineated. Major, secondary and micronutrients dynamics in soil is elucidated. Effect of biochar on crop yields in different soils across the globe discussed. Meta-analysis of data done to explore the influence of biochar on soil chemical properties and crop yields.